Use of Titanium Mesh for Reconstruction of Extensive Defects in Fronto-orbito-ethmoidal Fracture - Marao, Heloisa Fonseca; Gulinelli, Jessica Lemos; Silva Pereira, Cassiano Costa; Gomes de Souza Carvalho, Abrahao Cavalcante; Pinto Faria, Paulo Esteves; Magro Filho, Osvaldo [UNESP] (Lippincott Williams & Wilkins, 2010)
Traumatic injuries treatment of the fronto-naso-orbito-ethmoidal region has been one of the most challenging treatments within maxillofacial surgery, particularly of extensive orbital defects, very common in this type of pathologic condition. A 48-year-old man involved in a car collision presented an extensive bilateral fracture of the orbit medial wall, nasal bones, the nasal septum, and the frontal anterior table. The clinical and tomographic findings concluded the diagnosis of a maxilla and fronto-naso-orbito-ethmoidal fracture. Among the variety of biomaterials, the titanium mesh was elected because of the extension and magnitude of the bone defect, obtaining this way esthetic and functional results with better prognosis.
Keywords: Biomaterials; mesh; reconstruction